PENYELESAIAN SENGKETA KONTRAK BAGI PERUSAHAAN PASANGAN USAHA DALAM PEMBIAYAAN MODAL VENTURA TERHADAP USAHA KECIL DAN MENENGAH - Nurholis Majid; Nuzulia Kumala Sari; Halif (Jurnal Riset Multidisiplin Edukasi, 2025)
This research aims to investigate the various settlement options available to business partners in venture capital financing of small and medium enterprises (SMEs). By focusing on the context of venture capital financing, this research will identify and analyze settlement methods that can be applied by business partner companies to resolve conflicts that may arise in business relationships with SMEs. Through a qualitative approach, data will be collected from various sources, including interviews with relevant stakeholders, case studies, and related literature. An in-depth analysis will be conducted to understand the effectiveness and relevance of various settlement resolution methods, including arbitration, mediation, negotiation, and litigation. This research will also consider external and internal factors that influence settlement options, such as legal regulations, industry characteristics, and the dynamics of the relationship between business partner companies and SMEs. It is hoped that the results of this research will provide valuable insights for partner companies and SMEs in managing and resolving settlements effectively, thereby strengthening their business relationships and supporting the growth of the SME sector as a whole.